2006
DOI: 10.1302/0301-620x.88b8.17878
|View full text |Cite
|
Sign up to set email alerts
|

Distal femoral fractures treated by hinged total knee replacement in elderly patients

Abstract: Although the use of constrained cemented arthroplasty to treat distal femoral fractures in elderly patients has some practical advantages over the use of techniques of fixation, concerns as to a high rate of loosening after implantation of these prostheses has raised doubts about their use. We evaluated the results of hinged total knee replacement in the treatment of 54 fractures in 52 patients with a mean age of 82 years (55 to 98), who were socially dependent and poorly mobile. Within the first year after im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 39 publications
2
81
1
5
Order By: Relevance
“…In determining which to use, surgeons must consider multiple factors, including bone quality, fracture morphology, patient age, etc. Furthermore, some authors postulate that a constrained knee prosthesis could be a useful alternative to internal fixation in treating selected elderly patients with these fractures [1]. In preliminary studies, we found that a cemented prosthetic hip stem significantly reduced femoral fracture strength [14].…”
Section: Discussionmentioning
confidence: 69%
“…In determining which to use, surgeons must consider multiple factors, including bone quality, fracture morphology, patient age, etc. Furthermore, some authors postulate that a constrained knee prosthesis could be a useful alternative to internal fixation in treating selected elderly patients with these fractures [1]. In preliminary studies, we found that a cemented prosthetic hip stem significantly reduced femoral fracture strength [14].…”
Section: Discussionmentioning
confidence: 69%
“…Malvia et al, 53,54 reported a better functional outcome score with fewer complications regarding fractures at both the tibia and femur, but with little homogeneity in their implant choice. Appleton et al, 55 followed a similar patient cohort to ours, treated with three different hinged knee prostheses (2 with Kotz [Stryker-Howmedica, Newbury, UK], 38 with Guepar [StrykerHowmedica] and 14 using the Stanmore [Biomet, Bridgend, UK]). A similar surgical technique was used, but cement was used to "fill up" any bony deficit, rather than endoprosthetic replacement.…”
Section: Retrograde Im Fixationmentioning
confidence: 95%
“…2,[6][7][8] Although distal femur replacing total knee replacement, angled blade plates, and other methods have been successfully used to treat distal femur fractures in the elderly patients, locked plating and intramedullary nailing remain the current standards of operative care. [9][10][11][12] Nevertheless, high rates of complications and mortalities continue to be reported in all methods of internal fixation for distal femur fractures in the elderly patients. 1,2,8,13 Although multiple studies have assessed the biomechanical properties, functional scores, and complication rates of surgical treatment for distal femur fractures in the elderly patients, few studies have investigated the patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%